Життєва форма, пагоноутворення і ритм сезонного розвитку Potentilla anserina L. - ПАВЛОВА, НАДІЯ РОМАНІВНА (CHORNOMORSKI BOTANICAL JOURNAL, 2005)
Життєва форма, пагоноутворення і ритм сезонного розвитку Potentilla anserina L.